(untitled) (GYMNASIUM, 2008)
The need for as high as possible performances urges us to search for new means of improving the professional swimming technique. Special training with the conditions simulator has the goal of optimizing the growth in the arm’s strength, the traction length up to the physiological limit, bringing the arms into symmetry by other means than the ones used in the swimming pool, correcting the elements which are involved in the specific movement (length, force, time).